2022
DOI: 10.1002/ecs2.4083
|View full text |Cite
|
Sign up to set email alerts
|

Using seabird and whale distribution models to estimate spatial consumption of krill to inform fishery management

Abstract: Ecosystem dynamics at the northwest Antarctic Peninsula are driven by interactions between physical and biological processes. For example, baleen whale populations are recovering from commercial harvesting against the backdrop of rapid climate change, including reduced sea ice extent and changing ecosystem composition. Concurrently, the commercial harvesting of Antarctic krill is increasing, with the potential to increase the likelihood for competition with and between krill predators and the fishery. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 139 publications
(216 reference statements)
2
15
0
Order By: Relevance
“…In late autumn/ winter, massive, extremely dense aggregations of krill have been documented in the nearshore bays on the western side of the Antarctic Peninsula (Nowacek et al, 2011) coincident with where the krill fishery is known to operate at these times . Baleen whale concentrations (Johnston et al, 2012) mirror these supper aggregations of krill and whales consistently distribute in these places and forage in a manner that optimises energy gain (Friedlaender et al, 2013;Friedlaender et al, 2016;Tyson et al, 2016) Johannessen et al (2022 see also Warwick-Evans et al, 2022) estimate peak potential competition (calculated as humpback whales' per capita consumption multiplied by their abundance through the season, and krill catch through the season) in April, which corresponds with the highest values in our monthly spatial overlap index. Based on the assumption that whales spend 120 days in their Southern Ocean foraging areas (Lockyer, 1981), Johannessen et al (2022) calculated very limited humpback whale-fishery competition by May, but tracking data in this study and shows that some individuals remain in the region as late as July.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In late autumn/ winter, massive, extremely dense aggregations of krill have been documented in the nearshore bays on the western side of the Antarctic Peninsula (Nowacek et al, 2011) coincident with where the krill fishery is known to operate at these times . Baleen whale concentrations (Johnston et al, 2012) mirror these supper aggregations of krill and whales consistently distribute in these places and forage in a manner that optimises energy gain (Friedlaender et al, 2013;Friedlaender et al, 2016;Tyson et al, 2016) Johannessen et al (2022 see also Warwick-Evans et al, 2022) estimate peak potential competition (calculated as humpback whales' per capita consumption multiplied by their abundance through the season, and krill catch through the season) in April, which corresponds with the highest values in our monthly spatial overlap index. Based on the assumption that whales spend 120 days in their Southern Ocean foraging areas (Lockyer, 1981), Johannessen et al (2022) calculated very limited humpback whale-fishery competition by May, but tracking data in this study and shows that some individuals remain in the region as late as July.…”
Section: Discussionsupporting
confidence: 56%
“…The humpback whale population that uses waters off the Western Antarctic Peninsula is increasing rapidly (Pallin et al, 2018) and unprecedentedly dense 'super-aggregations' have been observed in this region (Nowacek et al, 2011). Spatial abundance models estimate around 19,000 individuals in this region in early summer (Johannessen et al, 2022; see also Warwick-Evans et al, 2022), a 5.1% per annum increase from the estimated 7,000 individuals in the same region in 2000 (Hedley et al, 2001;Johannessen et al, 2022). Their global IUCN Red List classification is Least Concern (Cooke, 2018).…”
Section: Humpback and Minke Whalesmentioning
confidence: 98%
“…However, the fishery does not operate across the entire Subarea, operating almost exclusively over shelf waters around the South Shetland Islands and northern Antarctic Peninsula (see Appendix 2), overlapping with most predator monitoring and krill survey effort (Trathan et al, 2022). Additionally, environmental conditions vary considerably across the latitudinal range of Subarea 48.1 (see Figure S4 in Warwick-Evans et al, 2022b). As such, we have not attempted to project species distributions into areas where there are no, or very few, observational data; extrapolating into geographic and environmental space without empirical data that constrain model projections could lead to biased results and unintended management consequences.…”
Section: Spatial Scalementioning
confidence: 99%
“…These distribution rasters were used to estimate spatially explicit krill consumption by each species, by combining estimated energy requirements calculated from Field Metabolic Rates (Shaffer, 2011) with estimates of the proportion of krill in the diet of each species (Croxall et al, 1985) and the energy density of krill (Clarke, 1980). Warwick-Evans et al (2022b) describe the approach to estimate krill consumption by three species of Pygoscelis penguins, fin whales Balaenoptera physalus, humpback whales Megaptera novaeangliae and Antarctic fur seals Arctocephalus gazella (Figure S1). For each cetacean species, sightings data were collected from ship surveys conducted between January and March 2013 -2020 by the Brazilian Antarctic Program (PROANTAR).…”
Section: Predator Krill Requirements Summermentioning
confidence: 99%
See 1 more Smart Citation